Development and validation of a composite disease activity score for measurement of muscle and skin involvement in juvenile dermatomyositis. (23rd January 2019) - Rosina, Silvia; Consolaro, Alessandro; van Dijkhuizen, Pieter; Pistorio, Angela; Varnier, Giulia Camilla; Bovis, Francesca; Nistala, Kiran; Maillard, Susan; Civino, Adele; Tsitsami, Elena; de Inocencio, Jaime; Jelusic, Marija; et al.
Abstract: Objective: To develop a composite DAS for JDM and provide preliminary evidence of its validity. Methods: The Juvenile DermatoMyositis Activity Index (JDMAI) is composed of four items: physician's global assessment of overall disease activity; parent's/child's global assessment of child's wellbeing; measurement of muscle strength; and assessment of skin disease activity. The score of the JDMAI is the arithmetic sum of the scores of each individual component. Six versions of the JDMAI were tested, which differed in the tools used to assess the third and fourth items. Validation procedures were conducted using three large multinational patient samples including a total of 627 patients. Results: The JDMAI was found to possess face and content validity, good construct validity, satisfactory internal consistency (Cronbach's alpha = 0.58–0.89), fair responsiveness to clinically important change (standardized response mean = 0.82–3.12 among patients improved) and strong capacity to discriminate patients judged as being in the state of inactive disease or low, moderate or high disease activity by the physician ( P < 0.001) or whose parents were satisfied or not satisfied with the course of their child's illness ( P < 0.001). Overall, the six versions of the JDMAI showed similar metrological performances in validation analyses. Conclusion: The JDMAI was found to possess good measurement properties in a large population of patients with a wide range of disease activity, and is, therefore, suitable for use in both clinical and research settings. The final version of the JDMAI will be selected after its prospective validation.